Constitutive expression of NF-κB inducing kinase in regulatory T cells impairs suppressive function and promotes instability and pro-inflammatory cytokine production. Issue 1 (December 2017) - Polesso, Fanny; Sarker, Minhazur; Anderson, Arian; Parker, David; Murray, Susan
Abstract CD4+ Foxp3+ regulatory T cells (Tregs) are indispensable negative regulators of immune responses. To understand Treg biology in health and disease, it is critical to elucidate factors that affect Treg homeostasis and suppressive function. Tregs express several costimulatory TNF receptor family members that activate non-canonical NF-κB via accumulation of NF-κB inducing kinase (NIK). We previously showed that constitutive NIK expression in all T cells causes fatal multi-organ autoimmunity associated with hyperactive conventional T cell responses and poor Treg-mediated suppression. Here, we show that constitutive NIK expression that is restricted to Tregs via a Cre-inducible transgene causes an autoimmune syndrome. We found that constitutive NIK expression decreased expression of numerous Treg signature genes and microRNAs involved in Treg homeostasis and suppressive phenotype. NIK transgenic Tregs competed poorly with WT Tregsin vivo and produced pro-inflammatory cytokines upon stimulation. Lineage tracing experiments revealed accumulation of ex-Foxp3+ T cells in mice expressing NIK constitutively in Tregs, and these former Tregs produced copious IFNγ and IL-2. Our data indicate that under inflammatory conditions in which NIK is activated, Tregs may lose suppressive function and may actively contribute to inflammation.